Tourism Resource Utilization and Recreational Innovation in a Geopark-Based Tourism Village - Arini Shofi Elmia; Endah Trihayuningtyas; Zulhelfa; Alexander Reyaan (Institut Pariwisata dan Bisnis Internasional, 2026)
The purpose of this research is to analyze and provide recommendations related to the development of recreational activities that can be developed in Karangsambung Tourism Village based on the potential of available tourism resources. Karangsambung Village still faces challenges in the utilization and management of its tourism resources, so the value of the benefits obtained is still limited. The research was conducted using a qualitative method with in-depth interviews with stakeholders. The collected data were tabulated and analyzed using the SWOT analysis deepening by IFAS and EFAS method. It is concluded that Karangsambung Village has tourism potential that can enable the tourism village enterprises to develop tourism products that can reach different market segments: family tourism, adventure seekers, and geotourism markets. Collaboration with BRIN is needed to strengthen the potential of Karangsambung Village as part of the UNESCO Global Geopark.